A THERMODYNAMIC ASPECTS OF METALLIC SECONDARY RAW MATERIALS RECYCLING POSSIBILITY - Miroslav Sokić; Ilija Ilić; Zvonko Gulišija; Nada Štrbac (Journal of Engineering & Processing Management, 2012)
Industrial products are made from different materials, therefore existing metallurgical plants are not always able to adequately process them. Knowing the thermodynamic parameters, possibility and degree of removal of contamininats from the base metal in the recycling process can be predicted. Such approach facilitates a decisions about products design, selection of recycling technology, reduces contamination and increases the system resources. In addition, recycling process becomes more profitable, reducing energy costs and increasing environmental protection. In this way, the use of resources becomes more sustainable.
Keywords: metallic secondary raw materials; contamination; racycling; refining; thermodynamics